Automobile interior PC alloy material resistant to corrosion of daily chemical products and preparation method of automobile interior PC alloy material

By adding specific components and process processing to PC/PET alloys, the problem of insufficient corrosion resistance of traditional PC/PET alloys in daily chemical products is solved, and a high corrosion resistance and gloss of automotive interior PC alloy materials are achieved.

CN119899512APending Publication Date: 2025-04-29FOSHAN XINSU NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510188448.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Traditional PC/PET alloys have poor corrosion resistance of daily chemicals, and while improving corrosion resistance, it is difficult to maintain the gloss of the plastic surface.

Method used

A composite system of polycarbonate and polyester is adopted, and components such as MBS toughening agent, polyolefin, PVDF and maleic anhydride grafted polyethylene are added on it, and PC alloy materials with corrosion resistance and gloss are prepared through extrusion and baking processes.

Benefits of technology

It achieves significantly improving its corrosion resistance to daily chemicals without affecting the gloss of the surface of PC alloy, ensuring that the surface is smooth under a long-term corrosion environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005279254000000061
    Figure BDA0005279254000000061
  • Figure BDA0005279254000000071
    Figure BDA0005279254000000071
  • Figure BDA0005279254000000072
    Figure BDA0005279254000000072
Patent Text Reader

Abstract

The invention relates to the field of PC materials, in particular to an automobile interior PC alloy material resistant to corrosion of daily chemical products and a preparation method thereof.In the automobile interior PC alloy material resistant to corrosion of the daily chemical products, on the basis of a PC-polyester composite system, polyolefin, PVDF and maleic anhydride grafted polyethylene are added, and the effect of overall resistance to corrosion of the daily chemical products is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of PC materials, and in particular to a PC alloy material for automobile interior decoration resistant to corrosion from daily chemical products and a preparation method thereof. Background Art

[0002] Polycarbonate / polyester alloy is a new type of alloy material. Due to the good mechanical properties of polycarbonate / polyester alloy, the fluidity of polycarbonate is improved by adding polyester, so that polycarbonate / polyester alloy can take into account the chemical resistance, heat resistance, rigidity of polycarbonate and the impact resistance and aging resistance of polyester. It is widely used in automotive interiors. For example, PC / PET composite alloy systems are used in vehicle lighting systems, dashboards, heating plates and other structures.

[0003] As an automotive interior panel, it is inevitable that corrosive materials such as cosmetics and car fragrances will spill during the driving process of the vehicle. However, the traditional PC / PET alloy has poor ability to resist corrosion from daily chemicals. After being corroded by daily chemicals, its surface glossiness is seriously affected. In order to reduce corrosion, one solution is to use a hydrophobic and oleophobic surface structure, but the hydrophobic and oleophobic surface usually requires it to have a high roughness. The microscopic roughness is used to reduce the spread of water droplets or oil droplets on the plastic surface. This method will seriously affect the glossiness of the plastic surface. Summary of the invention

[0004] In order to achieve the corrosion resistance of PC alloy without affecting the surface gloss of PC alloy, the present application provides an automotive interior PC alloy material resistant to corrosion by daily chemical products and a preparation method thereof.

[0005] First, the present application provides a PC alloy material for automotive interior decoration resistant to corrosion from daily chemical products, which comprises at least the following components in parts by mass:

[0006] 100 parts of PC composite system, of which 50 to 90 parts by mass are PC and the rest are polyester system;

[0007] MBS toughening agent 2-10 parts;

[0008] Lubricant 0.1~1 part

[0009] 5 to 10 parts of polyolefin; the density of the polyolefin is 0.88 to 0.93 g / cm 3 ;

[0010] PVDF 3-5 parts;

[0011] Maleic anhydride grafted polyethylene 1-3 parts

[0012] The alloy material is obtained by extruding the raw material and then baking the material at 120-150° C. for 2-6 hours.

[0013] Preferably, the mass fraction of the MBS-based toughening agent is 5 to 7 parts.

[0014] In the above scheme, a composite system of polycarbonate and polyester is used as the core component, and MBS-type toughening agents are used in the system to form a structural system with basic physical strength. On the basis of the above structural system, polyolefins and PVDF are added to improve the corrosion resistance of the system.

[0015] In this scheme, PVDF is selected because it has relatively similar processing conditions to the PC-polyester composite system, and the fluorine-containing molecular chain itself has strong corrosion resistance and barrier properties. Therefore, after its addition, it can effectively improve the corrosion resistance of the system and can have a good protective effect on the molecular chain under the long-term corrosion of organic solvents, surfactants and other materials. However, during the preparation process, two aspects need to be considered. First, PVDF itself needs to be located in the surface area to form a good protective effect, and excessive addition will have an adverse effect on the impact resistance. Second, the compatibility of PVDF system and PC composite system is relatively half. Therefore, in the above system, two additional components are added as auxiliary. One is a polyolefin with a lower density, and the other is maleic anhydride grafted polyethylene. Maleic anhydride grafted polyethylene is used as a compatibilizer to improve the overall uniformity of the system, and the low-density polyolefin can better form a blended phase with PVDF, thereby improving the overall co-processing performance, so that it will not precipitate alone during processing, affecting the gloss and strength of the system. At the same time, the blended phase can be better compatible with the mixed system of polyester and PC under the action of maleic anhydride grafted polyethylene, and has a more uniform structure as a whole.

[0016] At the same time, polyolefins also help promote the migration of PVDF molecular chains in the system, causing them to be distributed more close to the surface. Due to the softness of polyolefin molecular chains, the PVDF-polyolefin blend has better dispersion properties. Therefore, during the injection molding process, it will be more easily enriched in the surface area with lower energy and have a certain film-forming property. Therefore, PVDF can better exert its chemical corrosion resistance. At the same time, PTFE, which requires higher temperature processing, has worse dispersion performance in the system, is difficult to blend, requires higher processing temperature, and is not easy to form a smooth surface. Therefore, although it has better corrosion resistance, it still cannot replace PVDF here.

[0017] Among them, the polyolefin is preferably linear low-density polyethylene, which is easier to arrange neatly in the system to form a barrier structure, reducing the penetration of chemical substances into the plastic system, while also maintaining the processability of the system, improving the fluidity and ductility of the system, so that the prepared finished product has better surface gloss.

[0018] The polyester system is preferably one of PBT or PET, or a combination of the two, both of which can achieve good mechanical properties and corrosion resistance.

[0019] In the above scheme, the PVDF is not less than 6 g / 10 min at 230° C. The PVDF within this range has good processing performance with other components as a whole, and the prepared product has good gloss and uniformity.

[0020] Preferably, 7 to 12 parts by weight of nylon are also included.

[0021] Nylon has good barrier properties, and because of its structure of alternating soft and hard segments, it has good compatibility with both PVDF and PC phases. At the same time, its hard segment is prone to produce hydrophobic and oleophobic properties, thus blocking the plastic aging phenomenon caused by the migration of internal molecules to the surface during long-term use of the plastic, while providing a more glossy surface. Among various nylon materials, nylon MXD6 is preferably used, which has aromatic rings that can better provide rigidity and support performance, has less deterioration of overall mechanical properties, has better impact resistance, and has a higher surface gloss.

[0022] Preferably, it also includes 1 to 2 parts by weight of at least one of EVA, EEA, and EMA.

[0023] The use of vinyl ester copolymers containing ethylene segments can, on the one hand, improve the impact resistance so that the added polyolefin material does not detract from the impact resistance of the system as much as possible, while also further improving the compatibility of the system and reducing the degradation of mechanical properties caused by phase separation.

[0024] Preferably, the PC alloy material comprises no more than 10 parts by mass of an inorganic filler, wherein the inorganic filler is a whisker or nanoparticles with a particle size of no more than 10 μm.

[0025] The addition of a small amount of filler can improve rigidity and reduce production costs, while having no significant effect on mechanical properties and surface gloss.

[0026] In addition, the present application also relates to a method for preparing the above-mentioned automotive interior PC alloy material resistant to corrosion by daily chemical products. During the preparation, the above-mentioned materials are mixed, and then extruded and granulated at a temperature in the range of 240 to 280°C to obtain alloy pellets. After the alloy pellets are dried, they are injection molded by an injection molding machine to obtain the final product.

[0027] In summary, the combined system of polyolefin and PVDF in this application forms good glossiness and corrosion resistance on the surface of the system. When used as an automotive interior, it can maintain a smooth surface for a long time under the corrosion of daily chemicals, beverages and other materials. At the same time, in order to reduce the influence of polyolefin and PVDF on the mechanical properties of the system, nylon is additionally added to the system as a support system, and maleic anhydride grafted polyethylene and EVA\EEA\EMA are used as miscible materials, so that a more uniform miscible system can be formed in the system, and the corrosion resistance is better. DETAILED DESCRIPTION

[0028] The present application is further described through the following specific implementation methods.

[0029] In this plan, some materials are selected as follows:

[0030] PC 1250Y resin (Jiaxing Teijin)

[0031] PET FG730 resin (Jiangsu Yizheng Chemical Fiber)

[0032] MBS toughening agent S-2001 (Mitsubishi, Japan)

[0033] PVDF is obtained by suspension polymerization, and its melt flow index can be controlled by the degree of polymerization.

[0034] Various types of polyolefins are commercially available.

[0035] The following embodiments all involve automotive interior PC alloy materials resistant to corrosion from daily chemical products. In each embodiment, the following method is used for preparation: after mixing the materials, they are extruded through a twin-screw extruder in the range of 240 to 280°C, and then the strips are water-cooled, air-dried, and granulated to obtain alloy pellets. The alloy pellets are baked at 140°C for 3 hours and then injection-molded into standard strips by an injection molding machine.

[0036] Among them, the extrusion temperature can be determined according to the fluidity of the actual slurry. The higher the temperature, the better the fluidity of the slurry. However, in fact, too high a temperature will cause the molecular chain to break, and the material is prone to glass transition, which will also cause the surface roughness to increase. Therefore, when it is controlled at 240-280°C as a whole, the processing performance and surface gloss can be better balanced. In actual processing, multiple experiments can be conducted to determine the optimal processing temperature.

[0037] In the following examples, commercially available Dabao hand cream was applied to the sample and left for 48 hours, then washed with clean water and dried naturally, and the tensile strength, flexural modulus, notched Izod impact strength, heat deformation temperature (0.45 MPa) and glossiness before and after treatment were measured. The measurement standards for each parameter are as follows:

[0038] Tensile strength: ISO527-2

[0039] Flexural modulus: ISO178

[0040] Izod notched impact strength: ISO180

[0041] Heat distortion temperature (0.45MPa): ISO 75-2

[0042] Gloss: STMD523-2014.

[0043] First, in Example 1, the density is 0.925 g / cm 3 Linear low-density polyethylene (ExxonMobil Chemical) was used as the polyolefin, and the added amounts of polyolefin, PVDF and maleic anhydride grafted polyethylene were adjusted to verify the roles played by the above components in the system. In addition to polyolefin, PVDF and maleic anhydride grafted polyethylene, the specific gravity of the remaining components in this embodiment is as follows:

[0044] PC composite system 100 parts, including PC 70 parts, PET 30 parts

[0045] MBS toughening agent 5 parts

[0046] 0.5 parts of lubricant

[0047] 10 parts of silica filler, the particle size distribution of silica filler is 5-10 μm

[0048] In addition, the following additives can also be added to the following schemes:

[0049] 1.5 parts of transesterification inhibitor SAG

[0050] Light stabilizer HS-770 0.3 parts

[0051] Anti-UV agent UV-360 0.3 parts

[0052] Antioxidant 1076 0.5 parts

[0053] Ester exchange inhibitors, light stabilizers, UV inhibitors and antioxidants are all commonly used additives for plastic alloy systems. Their small addition will not have a significant effect on the performance of the system. Overall, the total amount added should not exceed 5% of the total plastic alloy system.

[0054] Table 1

[0055]

[0056]

[0057] Example 2: Based on Example 1, PET is replaced with PBT system with equal quality. The results are shown in Table 2.

[0058] Table 2

[0059]

[0060] Through Example 1 and Example 2, it is not difficult to see that in this application, the necessity of using a combination of polyolefin-maleic anhydride grafted polyethylene and PVDF is used. In the above scheme, the amount of PVDF is decisive for the glossiness and corrosion resistance of the surface. Therefore, in Examples 1-7 and 2-7 where PVDF is missing, it can be seen that the initial glossiness has decreased, and the decrease in various parameters under corrosion is more obvious. However, the amount of PVDF added should not be too much, otherwise the uniformity of the system will decrease to a certain extent, the bending modulus will increase, and the cantilever beam notch impact strength will decrease to a certain extent.

[0061] On the one hand, polyolefin improves the dispersion uniformity of PVDF and other components in the system. Too much addition (such as in Examples 1-5 and 2-5) will affect the strength of the system and have a significant adverse effect on the heat resistance of the system. Too little addition will also cause a significant decrease in various parameters of the system after being treated with daily chemical products. (such as in Examples 1-2 and 2-2)

[0062] In addition, the lack of maleic anhydride grafted polyethylene will lead to poor uniformity in the above system, which is specifically reflected in a certain degree of decline in various mechanical properties and heat resistance.

[0063] In addition, in the above experiment, it can be seen that PET alloy and PBT alloy have similar trends under the above system. On the whole, adding 10 to 50 parts of PET and PBT to every 100 parts of PC composite system can obtain a PC-polyester alloy system with different mechanical properties, and can be used in different scenarios. In subsequent experiments, a combination of 70 parts PC + 30 parts PET is fixed for experiment. The addition of toughening agent can improve the toughness of the system and reduce the rigidity of the system. The amount of toughening agent can be added in 2 to 10 parts at will, and other toughening agents, such as acrylic toughening agents, can also be selected. In subsequent experiments, 5 parts by mass of silicone toughening agent S-2001 were added as the standard.

[0064] Example 3. In this example, different polyolefins were used to conduct experiments based on Examples 1-3. The experimental results are shown in Table 3.

[0065] Table 3

[0066]

[0067] The abbreviations of the components are as follows:

[0068] LLDPE: low-density linear polyethylene;

[0069] PE: Polyethylene;

[0070] PP: Polypropylene;

[0071] EPDM: ethylene propylene diene copolymer rubber

[0072] EPM: Ethylene Propylene Rubber Institute

[0073] PB: Polybutene

[0074] From the above experiments, it can be seen that compared with polypropylene, polybutene or nonlinear low-density polyethylene, the use of linear low-density polyethylene has a certain improvement effect on the impact resistance and corrosion resistance of the system, especially the corrosion resistance has been significantly improved. It may be that linear low-density polyethylene is more likely to form a barrier structure in the system, reducing the penetration of organic molecules in daily chemical products.

[0075] In addition, the density of polyolefin should not be greater than 0.93g / cm 3 Otherwise, the system will become brittle, resulting in a certain decrease in strength and impact resistance. At the same time, if the density of polyolefin is too small, it will seriously affect the orderliness of the arrangement, which will have a significant adverse effect on the gloss.

[0076] Example 4. In this example, different types and qualities of nylon are additionally added on the basis of Examples 1-3. The specific experimental results are shown in Table 4.

[0077] Table 4

[0078]

[0079]

[0080] Through the above experiments, it can be seen that the addition of nylon has a certain effect on improving the impact resistance and weather resistance of the system, and can further reduce the corrosion of daily chemical products on the above PC alloy. Among them, considering various mechanical properties and surface gloss, nylon MXD6 performs best in the system, which may be related to the presence of aromatic rings therein.

[0081] Example 5. Based on Examples 4-8, this example further adds EVA, EEA or EMA of different types and qualities. The experimental results after adding are shown in Table 5.

[0082] Table 5

[0083]

[0084] In the above experimental results, we can see that in the above system, adding EVA\EMA\EAA can improve the impact resistance of the system, and has little effect on other properties, especially on the bending modulus, which shows that it has no obvious reduction in the elasticity of the system. However, if the amount is too large, it will have a negative impact on the initial gloss of the surface.

[0085] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A PC alloy material for automobile interior decoration resistant to corrosion from daily chemical products, characterized in that: It contains at least the following components by mass: 100 parts of PC composite system, of which 50 to 90 parts by mass are PC and the rest are polyester system; MBS toughening agent 2-10 parts; Lubricant 0.1~1 part 5 to 10 parts of polyolefin; the density of the polyolefin is 0.88 to 0.93 g / cm 3 ; PVDF 3-5 parts; 1 to 3 parts of maleic anhydride grafted polyethylene.

2. The PC alloy material for automobile interior decoration resistant to corrosion from daily chemical products according to claim 1, characterized in that: The PVDF is not less than 6 g / 10 min at 230°C.

3. The PC alloy material for automobile interior decoration resistant to corrosion from daily chemical products according to claim 1, characterized in that: The mass parts of the MBS toughening agent are 5 to 7 parts.

4. The PC alloy material for automobile interior decoration resistant to corrosion from daily chemical products according to claim 1, characterized in that: It also includes 7 to 12 parts by weight of nylon.

5. The PC alloy material for automobile interior decoration resistant to corrosion from daily chemical products according to claim 4, characterized in that: The nylon is selected from nylon MXD6.

6. According to the PC alloy material for automobile interior decoration resistant to corrosion from daily chemical products as described in claim 1, it is characterized in that: The polyolefin is linear low density polyethylene.

7. The PC alloy material for automobile interior decoration resistant to corrosion from daily chemical products according to claim 6, characterized in that: It also includes 1 to 2 parts by weight of at least one of EVA, EEA and EMA.

8. The PC alloy material for automobile interior decoration resistant to corrosion from daily chemical products according to claim 1, characterized in that: The polyester system is at least one of PET or PBT.

9. The PC alloy material for automobile interior decoration resistant to corrosion from daily chemical products according to claim 1, characterized in that: The PC alloy material comprises an inorganic filler in an amount not exceeding 10 parts by mass, wherein the inorganic filler is a whisker or nanometer particles with a particle size not exceeding 10 μm.

10. The method for preparing a PC alloy material for automobile interior decoration resistant to corrosion from daily chemical products according to any one of claims 1 to 9, characterized in that: The steps include: The above materials are mixed, and then extruded and granulated at 240-280° C. to obtain alloy pellets. After the alloy pellets are dried, they are injection molded by an injection molding machine to obtain the final product.